Evaluation of a Covalent Library of Diverse Warheads (CovLib) Binding to JNK3, USP7, or p53 - Klett T; Schwer M; Ernst LN; Engelhardt MU; Jaag SJ; Masberg B; Knappe C; Lämmerhofer M; Gehringer M; Boeckler FM (Dove Medical Press, 2024)
Theresa Klett,1,* Martin Schwer,1,* Larissa N Ernst,1,* Marc U Engelhardt,1 Simon J Jaag,2 Benedikt Masberg,2 Cornelius Knappe,2 Michael Lämmerhofer,2 Matthias Gehringer,3,4 Frank M Boeckler1,5 1Laboratory for Molecular Design & Pharmaceutical Biophysics, Institute of Pharmaceutical Sciences, Department of Pharmacy and Biochemistry, Eberhard Karls Universität Tübingen, Tübingen, 72076, Germany; 2Pharmaceutical (Bio-) Analysis, Institute of Pharmaceutical Sciences, Department of Pharmacy and Biochemistry, Eberhard Karls Universität Tübingen, Tübingen, 72076, Germany; 3Pharmaceutical Chemistry, Institute of Pharmaceutical Sciences, Department of Pharmacy and Biochemistry, Eberhard Karls Universität Tübingen, Tübingen, 72076, Germany; 4Medicinal Chemistry, Institute for Biomedical Engineering, Eberhard Karls Universität Tübingen, Tübingen, 72076, Germany; 5Interfaculty Institute for Biomedical Informatics (IBMI), Eberhard Karls Universität Tübingen, Tübingen, 72076, Germany*These authors contributed equally to this workCorrespondence: Frank M Boeckler, Laboratory for Molecular Design & Pharmaceutical Biophysics, Institute of Pharmaceutical Sciences, Department of Pharmacy and Biochemistry, Eberhard Karls Universität Tübingen, Auf der Morgenstelle 8 (Haus B), Tübingen, D - 72076, Germany, Tel +49 7071 29 74567, Email frank.boeckler@uni-tuebingen.dePurpose: Over the last few years, covalent fragment-based drug discovery has gained significant importance. Thus, striving for more warhead diversity, we conceived a library consisting of 20 covalently reacting compounds. Our covalent fragment library (CovLib) contains four different warhead classes, including five α-cyanoacacrylamides/acrylates (CA), three epoxides (EO), four vinyl sulfones (VS), and eight electron-deficient heteroarenes with a leaving group (SNAr/SN).Methods: After predicting the theoretical solubility of the fragments by LogP and LogS during the selection process, we determined their experimental solubility using a turbidimetric solubility assay. The reactivities of the different compounds were measured in a high-throughput 5,5'-dithiobis-(2-nitrobenzoic acid) DTNB assay, followed by a (glutathione) GSH stability assay. We employed the CovLib in a (differential scanning fluorimetry) DSF-based screening against different targets: c-Jun N-terminal kinase 3 (JNK3), ubiquitin-specific protease 7 (USP7), and the tumor suppressor p53. Finally, the covalent binding was confirmed by intact protein mass spectrometry (MS).Results: In general, the purchased fragments turned out to be sufficiently soluble. Additionally, they covered a broad spectrum of reactivity. All investigated α-cyanoacrylamides/acrylates and all structurally confirmed epoxides turned out to be less reactive compounds, possibly due to steric hindrance and reversibility (for α-cyanoacrylamides/acrylates). The SNAr and vinyl sulfone fragments are either highly reactive or stable. DSF measurements with the different targets JNK3, USP7, and p53 identified reactive fragment hits causing a shift in the melting temperatures of the proteins. MS confirmed the covalent binding mode of all these fragments to USP7 and p53, while additionally identifying the SNAr-type electrophile SN002 as a mildly reactive covalent hit for p53.Conclusion: The screening and target evaluation of the CovLib revealed first interesting hits. The highly cysteine-reactive fragments VS004, SN001, SN006, and SN007 covalently modify several target proteins and showed distinct shifts in the melting temperatures up to +5.1 °C and − 9.1 °C. Keywords: covalent fragment-based drug discovery, differential scanning fluorimetry, 5,5'-dithiobis-(2-nitrobenzoic acid), intact protein mass spectrometry, glutathione